Influence of Sustainable Agriculture Practices, Water Management, and Organic Seedling Availability on Yields in Bandung Regency Organic Farms - Eddy Silamat; Hernawati Hernawati; Rival Pahrijal (Westscience Press, 2024)
This study investigates the impact of organic seedling availability, sustainable agriculture practices, and water management on the yields of organic farms in Bandung Regency. Using a quantitative approach, data were collected from 230 organic farmers and analyzed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). The results reveal that all three factors significantly and positively affect farm yields. Water management had the strongest influence, followed by organic seedling availability and sustainable agriculture practices. These findings highlight the critical role of resource management in enhancing the productivity of organic farms. The study suggests that improving access to organic seedlings, promoting sustainable farming techniques, and investing in efficient water management systems can lead to better farm performance and sustainability. The research offers practical insights for policymakers and agricultural stakeholders seeking to optimize organic farming in the region.